"Wetlands". Survey in the Coastal Lagoon of Orbetello (Grosseto, Tuscany) and the Argentario Mount (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2014)
“Paesaggi d’Acque” (Wetlands) Survey Project has been carried out by the University of Milan around the coastal lagoon of Orbetello (Grosseto, Tuscany) and the Argentario Mount. It aims at understanding the human-environment relationships in this special and marginal territory, as well as at reconstructing its ancient landscapes from Palaeolithic to Late Roman period. Archaeological data have been employer on a digital GIS system, to permit diacrhonical reading of landscape and to help land protection.
Keywords: Wetlands; Orbetello; survey; GIS; landscape